2019
DOI: 10.1186/s12935-019-0744-y
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulated lncRNA XIST contributes to progression of cervical cancer via regulating miR-140-5p and ORC1

Abstract: Background The study purpose was to make investigation into the influence of XIST on cervical cancer progression and what’s more its potential mechanism. Methods The cervical cancer data sets (lncRNA, miRNA, and mRNA) obtained from TCGA were analyzed with the “mixOmics” R package. Then, the expression of XIST, miR-140-5p, and ORC1 were detected using qRT-PCR and western blot in both tissues and cervical cancer cell lines (Hela and C33A) to ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 37 publications
(44 reference statements)
2
63
0
Order By: Relevance
“…They can function as molecular sponges, scaffolds, and guides for interactions with proteins, mRNAs, or microRNAs (miRNAs), thereby regulating the expression of target genes (Anastasiadou et al, 2018). Accumulated evidence indicates that many lncRNAs are aberrantly expressed in cervical cancer (Chen et al, 2019;Zhang X. et al, 2019). Alterations in the expression of lncRNAs are involved in cervical carcinogenesis and cancer progression by playing tumorsuppressive or oncogenic roles (Aalijahan and Ghorbian, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…They can function as molecular sponges, scaffolds, and guides for interactions with proteins, mRNAs, or microRNAs (miRNAs), thereby regulating the expression of target genes (Anastasiadou et al, 2018). Accumulated evidence indicates that many lncRNAs are aberrantly expressed in cervical cancer (Chen et al, 2019;Zhang X. et al, 2019). Alterations in the expression of lncRNAs are involved in cervical carcinogenesis and cancer progression by playing tumorsuppressive or oncogenic roles (Aalijahan and Ghorbian, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs bind to the seed sequences of the 3’‐untranslated region of their target messenger RNAs (mRNAs) and mediate the degradation of corresponding mRNAs or inhibit their translation . Multiple studies have reported the correlation between aberrant expression of miRNAs and cancer progression . Furthermore, free miRNAs could be detected in human body fluids like serum.…”
Section: Introductionmentioning
confidence: 99%
“…8 Multiple studies have reported the correlation between aberrant expression of miRNAs and cancer progression. [9][10][11][12] Furthermore, free miRNAs could be detected in human body fluids like serum. The expression profile of cancer patients' serum miRNAs differs significantly from healthy people's expression profile.…”
Section: Introductionmentioning
confidence: 99%
“…They also found that SOX21-AS1 promoted cervical cancer progression and could be used as a potential prognostic biomarker for patients with cervical cancer. Also, Chen et al 16 demonstrated that lncRNA X-inactive specific transcript (XIST) contributed to progression of cervical cancer by sponging miR-140-5p. Here, we detected lncRNA TMPO-AS1 expression in cervical cancer cells and found that TMPO-AS1 was highly expressed in cervical cancer cells.…”
Section: Discussionmentioning
confidence: 99%